Urgensi Hukum Siber terhadap Kelompok TNI dalam melaksanakan Tugas Pokok: UU ITE No. 11 Tahun 2008 Jo No. 19 Tahun 2016 - Firman Halawa (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
The law on information and electronic transactions (UU-ITE) is a product of laws that are applicable to solving legal problems in the Internet world. In its development, information and communication technology for crimes and crimes in cyberspace is a challenge that is anticipated in order protect resources within the TNI. The TNI is required to have cyber defense capabilities order to increase deterrence and prevention of war or cyber-attacks against the TNI or national cyber defense in carrying out TNI's Main tasks. The normative juridical method is carried out through literature studies that examine (mainly) secondary data, both in the form of legislation and research results, assessment results and other references.